How do you solve -[ 3x + ( 5x + 3) ] = 9- ( 6x + 1)?

1 Answer
Jan 3, 2018

x=-\frac{11}{2}

Explanation:

-[3x+(5x+3)]=9-(6x+1)

The first round brackets are preceded by the + sign, so they can be removed leaving the sign of the contained terms unchanged:
-[3x+5x+3]=9-(6x+1)

While for those preceded by the - we must invert the signs of terms:
-[3x+5x+3]=9-6x-1

Same reasoning for square brackets (- sign before):
-3x-5x-3=9-6x-1

Now let's move all the terms from the second part to the first part of equation changing the sign
-3x-5x-3-9+6x+1=0

Sum all terms with the x togheter and all the constants (terms whitout x toghter:
-2x-11=0

Move -11 to the other side by changing the sign
-2x=11

Multiply both sides by -1 to change the sign (the term x should be positive for readability):
2x=-11

Final result:
x=-\frac{11}{2}